Phenological assessment of early-maturing soybean accessions (Glycine max (L.) Merr.) under the conditions of Moscow Province - E. V. Vlasova; Yu. V. Gorbunova; I. V. Seferova (Труды по прикладной ботанике, генетике и селекции)
Background. The range of early-maturing cultivars suitable for the Non-Black-Earth Zone of the Russian Federation (RF) is extremely limited. The main method of finding sources of earliness for crop production and breeding is the evaluation of the gene pool under the required conditions.Materials and methods. The objects of the study were 81 soybean accessions from the VIR collection, precharacterized as early-ripening under the conditions of Northwest Russia. The studies were carried out in 2018–2020 as field trials under the conditions of Moscow Province.Results. Soybean accessions were characterized by the duration of the emergence-to-flowering (37–53 days), flowering-to-ripening (50–85 days) and emergence-to-ripening (81–130 days) periods. The extreme ripening dates for the accessions were observed from August 20 to October 5, while the maximum duration from emergence to ripening was from 93 to 139 days. The highest sum of active temperatures above 10°C for a growing season ranged from 1642 to 2189°C. Most of the studied accessions were characterized by a short emergence-to-flowering period. Therefore, the differences among accessions in the duration of the growing season were mainly due to the different lengths of their flowering-to-ripening period.Conclusion. Soybean seeds should ripen no later than the first 10 days of September for a stable harvest under the weather conditions of the Russian Non-Black-Earth Zone. There were 32 accessions from breeding centers of the RF, Belarus, Poland, Germany, Sweden, and the U.S. that met these requirements during the three years of observations. The selected accessions demonstrated a short emergence-to-flowering period of 37–48 days, and the length of their flowering-to-ripening period of 50–66 days, on average for three years. They can be used as sources of earliness in soybean breeding.